10x-2x-15=27+3x

Simple and best practice solution for 10x-2x-15=27+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x-2x-15=27+3x equation:


Simplifying
10x + -2x + -15 = 27 + 3x

Reorder the terms:
-15 + 10x + -2x = 27 + 3x

Combine like terms: 10x + -2x = 8x
-15 + 8x = 27 + 3x

Solving
-15 + 8x = 27 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-15 + 8x + -3x = 27 + 3x + -3x

Combine like terms: 8x + -3x = 5x
-15 + 5x = 27 + 3x + -3x

Combine like terms: 3x + -3x = 0
-15 + 5x = 27 + 0
-15 + 5x = 27

Add '15' to each side of the equation.
-15 + 15 + 5x = 27 + 15

Combine like terms: -15 + 15 = 0
0 + 5x = 27 + 15
5x = 27 + 15

Combine like terms: 27 + 15 = 42
5x = 42

Divide each side by '5'.
x = 8.4

Simplifying
x = 8.4

See similar equations:

| 4(w+9)=20 | | 12g^2+16g-3=0 | | 6+m=21 | | 9v^2-55v+50=0 | | a=bcW+x-y | | 11-3-2x+3x=4x-4 | | 7x-58=2x-8 | | (5x)-6-7x=2 | | 6x+(x-16)=180 | | 10+50m=110 | | 0.33+2=6x-73 | | -55.2=6.9c | | 4(4x+6)=2(8x+12) | | 2(6c+8)=4+6c | | 26=b-16 | | 3t^2-9t=12 | | 50+10m=110 | | V=(3.14)(2*2)(150) | | (3x^5)-2=0 | | 2(5x-1)+5x-1+3x=78 | | 1.4+t=0 | | 20+8m=92 | | -7(3x+9.5)=-18.5 | | 5*13-3*(20+1.666666666)= | | .7x=.14 | | 7k^2+39k-18=0 | | 5y+(-2x)=12 | | (x+87)+2x=180 | | x^2+5x-8=6x+4 | | 5p+525=1500 | | -16t^2+128t+9=0 | | 1.32/0.5=26.4 |

Equations solver categories